Bioactive compounds and biological actions in edible flower species - Ribeiro Fonseca , Barbara; Vidal Martins, Marcos (Seven Editora, 2023)
Introduction: Edible flowers are used in food in many regions, and over the years, their consumption has increased, as they add color and beauty to dishes, they also contribute to human health, as they are rich in bioactive compounds. Objective: Thus, the objective was to survey the literature on bioactive compounds from edible flowers, as well as expose some of biological activities. Methodology: A search for scientific research was carried out through electronic databases: SciElo, PubMed, Lilacs and Web of Science, using the descriptors: Flores comestíveis “Edible flowers”, Compostos bioativos “Bioactive compounds” and Fitoquímicos “Phytochemicals”, combined by Boolean operator “AND”. We used studies available in full, in Portuguese or English, which contained two of the three descriptors. Results: Studies have shown that edible flowers have several bioactive compounds, highlighting the presence of flavonoids, anthocyanins, carotenoids, and phenolic acids that have biological actions (anti-inflammatory, antioxidant, anti-hyperglycemic, anti-obesity, antibacterial, for example). Conclusion: The physical- chemical and nutritional characterization studies have been growing, but there is still a lack of studies on native species in Brazil, to know their biological properties and encourage both the consumption and the production of edible flowers. DOI: 10.56238/pacfdnsv1-027